Digitally Empowered: New patterns of sourcing and expertise in cultural journalism and criticism - Silva, Dora Santos (Journalism practice, 2019)
In January 2013, Peter Bradshaw, a film critic for The Guardian, said that Twitter users had become the favourite "critics" of the film industry. The implicit concern in this article on a subject dear to cultural journalism-"Would be criticism bankrupted when we are all 'critics' on the Web?"-became evident in the following years. It is pertinent, then, to explore the media answer not only to this subject but both to sourcing and expertise in general in the culture section. Did they embrace these new news sources (and which) that emerged in the digital environment, such as the reader, blogs or artists tweets? Assuming the first hypothesis, how did they include them in their editorial model, alongside with the "traditional" experts and sources? We conducted a content analysis to the culture section of an international media-The Guardian-between 2014 and 2016 (n = 992), identifying the role of what we would like to call digitally empowered sources and the presence of new "experts" in cultural criticism. We concluded that these digitally empowered sources play an important role in the overall editorial, business and engagement media's strategy and are deeply engaged with a new digital feature: hypertextuality. New patterns of expertise also reflect an editorial positioning supported in an engagement strategy and in the recognition of the readers' added value to content.